2017
DOI: 10.3201/eid2302.161203
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Antibiotic Resistance inShigellaspp. from Infected New York City Residents, New York, USA

Abstract: Approximately 20% of Shigella isolates tested in New York City, New York, USA, during 2013–2015 displayed decreased azithromycin susceptibility. Case-patients were older and more frequently male and HIV infected than those with azithromycin-susceptible Shigella infection; 90% identified as men who have sex with men. Clinical interpretation guidelines for azithromycin resistance and outcome studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 5 publications
2
28
1
1
Order By: Relevance
“…Among men with shigellosis, 37% overall and 76% of those with DSA-Shigella were either PLWH or had a recent STD. These findings are consistent with other shigellosis outbreak reports among MSM but present more robust estimates of recent STD prevalence among shigellosis patients (20,22,27). Co-infection with STDs is of particular concern because azithromycin is recommended as a treatment for chlamydia, as well as for gonorrhea in conjunction with ceftriaxone (30).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Among men with shigellosis, 37% overall and 76% of those with DSA-Shigella were either PLWH or had a recent STD. These findings are consistent with other shigellosis outbreak reports among MSM but present more robust estimates of recent STD prevalence among shigellosis patients (20,22,27). Co-infection with STDs is of particular concern because azithromycin is recommended as a treatment for chlamydia, as well as for gonorrhea in conjunction with ceftriaxone (30).…”
Section: Discussionsupporting
confidence: 89%
“…However, resistance profiles differed across groups at risk for shigellosis; 42 of the 43 domestically acquired DSA-Shigella cases in Minnesota occurred among men, 60% of whom were also infected with HIV. This trend has been observed in other jurisdictions and has implications for clinical testing, public health surveillance, case management, and prevention efforts (27)(28)(29).…”
Section: Discussionmentioning
confidence: 63%
“…28 To reduce the emergence of resistance, antibiotics should be avoided for treating Shigella infections, except in patients with severe shigellosis or cases at risk for systemic infection. 29 In our study, nine (6.3%) S. sonnei were nonsusceptible to all of the tested antibiotics. Our analysis also showed that the multidrug resistance was more frequent among S. sonnei as compared to S. flexneri.…”
Section: Discussionmentioning
confidence: 46%
“…Although young children were at highest risk of Shigella related mortality in studies in Bangladesh [ 10 ] and the United States, some data now suggest an association between shigellosis severity and HIV-infection [ 11 , 12 ]. Additional reports have shown disproportionate levels of shigellosis among men who have sex with men (MSM), particularly those with HIV infection [ 13 , 14 ], and high levels of antimicrobial resistance in Shigella isolates from MSM [ 15 , 16 ]. However, it remains unclear whether disparities in shigellosis severity exist among adult populations.…”
Section: Introductionmentioning
confidence: 99%